O Instituto de Ação da Cidadania dos Funcionários do Banco do Nordeste no Assentamento Unidos de Santa Bárbara: um estudo de caso - Fick, Vera Maria Soares (2005)
Throughout history, the Brazilian State has adopted different strategies in issues related to the economic development of the Northeast Region. The creation, in 1909, of the National Department of Works Against Drought (DNOCS), the former Inspection of Works Against Drought, the São Francisco Hydroelectric Company (CHESF) in 1945, Banco do Nordeste in 1952, and the Superintendency (SUDENE) in 1959 are examples of these actions, implemented until the middle of the last century. In the last decades, the actions of the federal government in the region have prioritized already favored groups, or sectors of activities considered dynamic and competitive, to the At the same time as they have provided an industrial development envelope sustained, above all, by the fiscal renunciation and, often, by the force of workers submitted to new forms of exploitation and control of labor. [...]